Reliability of a Novel Magnetic Resonance Imaging Scoring System to Evaluate Patellofemoral Osteoarthritis - Uppstrom, Tyler J.; Palhares, Guilherme; Cecere, Robert; Anzillotti, Giuseppe; Fletcher, Connor F.; Davidson, Emily; Burge, Alissa; Strickland, Sabrina M. (The Journal of Knee Surgery, 2025)
Knee osteoarthritis is a common degenerative or posttraumatic condition associated with significant pain and disability among patients. Isolated patellofemoral osteoarthritis (PFOA) occurs in approximately 24% of women and approximately 11% of men aged >55 years presenting with knee pain. In contrast to the tibiofemoral compartments, the current literature lacks a reliable magnetic resonance imaging (MRI) scoring system for quantitative evaluation of patellofemoral cartilage degeneration. This study aimed to describe, apply, and assess the interobserver reliability of a novel MRI scoring system for assessment of the patellofemoral cartilage. Patients who underwent patellofemoral arthroplasty for isolated PFOA between January 2012 and December 2021 were identified. Preoperative MRI scans were performed on 3.0-Tesla magnets utilizing dedicated extremity coils and standardized clinical imaging protocols consistent with International Cartilage Regeneration and Joint Preservation Society (ICRS) guidelines for the assessment of articular cartilage. A novel semiquantitative MRI patellofemoral scoring system included assessment of patellar and trochlear cartilage, bony architecture, patellofemoral alignment, and synovitis. Interobserver agreement was assessed using Cohen's Kappa coefficient for categorical variables, and the intraclass correlation coefficient (ICC) was used for the total score. A total of 72 knee MRIs were included in the final analysis. Patellar bone edema (kappa = 0.61) and patellar cysts (kappa = 0.59) demonstrated moderate interobserver agreement. All cartilage features, trochlear bone edema and cysts, osteophytes, subchondral remodeling, patellar height, and synovitis demonstrated good interobserver agreement (kappa > 0.61). Patellofemoral alignment and total score demonstrated excellent interobserver agreement (kappa > 0.81). The novel MRI scoring system for PFOA proposed in this study represents a comprehensive method to assess patellofemoral joint cartilage degeneration, including evaluation of patellar and trochlear cartilage changes, bony architecture, patellofemoral alignment, and synovitis. Importantly, all features of the scoring system demonstrated at least moderate interobserver agreement, with the majority of variables and total score demonstrating good to excellent agreement.
Keywords: patellofemoral; osteoarthritis; arthroplasty; magnetic resonance imaging